Чигитли пахтани сақлаш ва ишлатиш ҳолати ва истиқболлари (SCIENCE and SOCIETY, 2024)
The article analyzes foreign technologies for storing raw cotton collected as a result of the mechanization of cotton harvesting, and also provides recommendations for the creation and implementation of technologies for extracting high-quality fiber for spinning.